Biogenic and Abiogenic Origins of Authigenic Pyrite of Gombe Inlier, Gongola Arm, Upper Benue Trough N.E Nigeria. (Journal of Pure and Applied Sciences (Science Forum), 2023)
This study constrains the origin of pyrite of the Gombe In-lier to either biogenic orabiogenic using the analytical techniques Scanning Electron Microscopy and EnergyDispersive X-ray Spectroscopy and stable sulfur isotopes studies. The stable isotopecompositions are useful indicators of the pathways of both biogenic and abiogenicpyrite formation. Textural and compositional information preserved in sedimentarypyrite from sediment-hosted ore deposits has contributed to elucidate theirenvironment of formation. Backscattered SEM images of pyrite samples of thisstudy were compared with that of the Huitrin Formation, Neuquén Basin inArgentina which is Aptian in age together with that of the offshore core samples ofthe Captain sands of Western Moray Frith Basin, United Kingdom with an Aptianage, the Valanginian (Lower Cretaceous) Wealden group of the Wessex Basin inDorset, United Kingdom, the Turonian Afowo Formation in the Dahomey Basin ofNigeria. Result showed that in all SEM images, micrographs indicate either euhedralor framboids pyrites. Their respective isotopes results (mean) were also compared.The isotope result places the samples of the Gombe inlier with strong evidence thatthey could either have an origin that is biogenic or abiogenic, with a positive δ34Svalues signifying a closed system sulfate reduction during the pyrite mineralizationof the area and of low temperature mineralization.